Management of Tetanus Patients in the Intensive Care Unit : A Case Report - Hanafia, Mochamad Fauzi; Adiyanto, Bowo (The International Journal of Medical Science and Health Research, 2024)
We report a case of a 41-year-old male patient with a history of a nail puncture wound who presented to the Emergency Department (ED) with complaints of generalized body stiffness. The patient experienced worsening stiffness, particularly in the neck, jaw, back, and abdomen. He was diagnosed with tetanus and received initial treatment with human tetanus immunoglobulin (HTIG) and antibiotics. The patient was admitted to the intensive care unit (ICU) due to the risk of recurrent seizures and airway obstruction. During the treatment, he developed several complications, including pneumonia and hematemesis. Supportive care was provided, including adequate nutrition, prevention of pressure sores, and physiotherapy. The patient showed improvement after the administration of magnesium sulfate (MgSO4) to control spasms and autonomic dysfunction. He was successfully weaned off the ventilator and discharged after 40 days of intensive care.